Life Cycle Assessment and Characterization of Tincal Ore Reinforced Polyester and Vinylester Composites - Yılmaz, Emrah; Aydoğmuş, Ercan; Demir, Ahmet (My University, 2023)
In this study, the quality performance, compressive strength, surface hardness, electrical conductivity, and life cycle assessment (LCA) of the composites produced by reinforcing tincal (Na2B4O7.10H2O) into polyester and vinylester resins at different rates have been determined. Tincal ore, which is ground with a particle size of 74-149 microns, is dried in an oven at 105 °C for 2 hours and then added to the resins at the ratios of 0 wt.%, 1 wt.%, 2 wt.%, and 3 wt.%. According to the results obtained, it has been determined that the compressive strength and Shore D hardness of the composite raises as the tincal mass ratio increases up to certain amounts. According to the mechanical test results, it is found that 3 wt.% tincal reinforcement maximized the compressive strength of the polyester composite, and 2 wt.% tincal reinforcement maximized the compressive strength of the vinylester composite. In the electrical conductivity test results, it is seen that the first relaxation time of the polyester composite is 2.14·10-4 s and the relaxation times of vinylester composite vary between 10-4 and 10-6 seconds. LCA results showed that vinylester composite had more environmental effects than polyester composite except for ozone layer depletion (ODP) effect. Although there is a partial increase (<0.5%) in the environmental impact of composites with tincal reinforcement, it is thought that the increase in the technical performance of the composites will tolerate this partial increase.
Keywords: Compressive strength; hardness; life cycle assessment; dielectric properties; Polyester; vinylester; tincal